Enhanced High-Density Line Spectral-Domain Optical Coherence Tomography Imaging of the Vitreoretinal Interface: Description of Selected Cases. (1st November 2016) - Kim, Yu Cheol; Harasawa, Mariana; Salcedo-Villanueva, Guillermo; Siringo, Frank S.; Paciuc-Beja, Miguel; Olson, Jeffrey L.; Mandava, Naresh; Quiroz-Mercado, Hugo
Abstract: Purpose : We introduce a new method to observe the morphologic features of the vitreous with spectral-domain optical coherence tomography (SD-OCT) by evaluating and describing the posterior vitreous structure of various selected cases using enhanced high-density (HD) line mode. Methods : This is a descriptive case series of SD-OCT images with enhanced HD line at Denver Health Medical Center, University of Colorado School of Medicine, in 2014. The medical records with ocular images for these patients were analyzed. Results : Enhanced HD line in vitreoretinal mode with SD-OCT offered wide images with well-visible vitreoretinal interface. The posterior precortical vitreous pocket (PPVP), often mistaken as a posterior vitreous detachment on standard retina-based cross line mode, was easily identified. Vitreomacular adhesion and traction, absence or presence of connecting channels between PPVP and Cloquet's canal, liquefied vitreous lacuna, and emulsified silicone oil droplet-layer could be observed. Conclusions : SD-OCT using enhanced HD line in vitreoretinal mode enables clear visualization of the posterior vitreous structure and often reclassifies patients previously thought to have a posterior vitreous detachment.